Early and immediate loading of titanium implants with fluoride-modified surfaces: results of 5-year prospective study - Mertens, Christian; Steveling, Helmut (Clinical oral implants research, 2011)
Objective: Multiple experimental and animal studies have shown that topographic, mechanical and chemical properties of implant surfaces lead to in vivo responses such as increased bone formation, increased bone anchorage and reduced healing time. A fluoride modification of the titanium implant surface also seems to positively influence bone anchorage as compared with unmodified titanium implants. Using implant survival and marginal bone loss as primary outcome parameters, the purpose of the present prospective study was to investigate whether a fluoride modification of the titanium implant surface has positive clinical effects. Materials and methods: The 17 patients included in this study received 49 Astra Tech OsseoSpeed™ implants for various indications in the maxilla and mandible. Implants were either loaded immediately or after a mean healing period of 9.56 weeks. Fifteen patients were followed up clinically including radiographic examination for 5 years. Forty-two implants were assessed for implant survival, marginal bone loss, surgical and/or prosthetic complications, presence or absence of plaque, signs of inflammation and size of the papilla. Results: Of the original 17 patients, 15 patients were available for the full 60-month follow-up. One early implant failure occurred, leading to an implant survival rate of 97%. Radiographic analyses demonstrated stable bone conditions with a mean marginal bone loss of 0.1 mm (SD 0.4 mm, min −0.7 mm, max 1.7 mm) after 5 years of function. Immediately loaded implants did not show a different mean marginal bone loss as compared with implants that were not loaded immediately. Repeated soft-tissue examinations revealed healthy conditions in terms of 6.1% plaque and 4.2% of the implants with signs of inflammation at the 5-year control. Discussion: Implants used in this study had high survival and success rates after 5 years. Marginal bone was well maintained, irrespective of the loading regime.
Gesehen am 18.08.2022